2022
DOI: 10.3934/environsci.2022035
|View full text |Cite
|
Sign up to set email alerts
|

Carbofuran residues in soil and consumption risks among farmers growing vegetables in Ubon Ratchathani Province, Thailand

Abstract: <abstract> <p>Farmers in Khi Lek Subdistrict, Muang District, Ubon Ratchathani Province, Thailand have been known to persistently use pesticides, especially carbofuran, in their agricultural fields. This indeed poses a risk to farmers' health and ecosystem. However, there has been no report pointing out this problem. The purpose of this study was to determine carbofuran residues in soil in four villages in Khi Lek Subdistrict, Muang District, Ubon Ratchathani Province, Thailand, where pesticides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This study demonstrated that sunlight can enhance the photodegradation of carbofuran in water, and hydrolysis is the main route for carbofuran degradation in water. Findings of previous studies suggested that 3-keto carbofuran and 3-hydroxy carbofuran are the most stable carbofuran metabolites (Ramasubramanian and Paramasivam 2018;Mohamed et al 2021;Boonkhao et al 2022).…”
Section: Determination Of Rate Of Degradation K and Half-life Of Carb...mentioning
confidence: 98%
“…This study demonstrated that sunlight can enhance the photodegradation of carbofuran in water, and hydrolysis is the main route for carbofuran degradation in water. Findings of previous studies suggested that 3-keto carbofuran and 3-hydroxy carbofuran are the most stable carbofuran metabolites (Ramasubramanian and Paramasivam 2018;Mohamed et al 2021;Boonkhao et al 2022).…”
Section: Determination Of Rate Of Degradation K and Half-life Of Carb...mentioning
confidence: 98%